Intradialytic Exercise dan Outcome pada Pasien yang Menjalani Hemodialisis - Tatu Meri; Tuti Herawati; Lestari Sukmarini; I Made Kariasa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to study the effect of intradialysis exercise on patients undergoing hemodialysis. The research method used is a literature search. The research results were published in English and Indonesian journals from 2018 to 2022. The literature search used PICO references in several databases, such as ScienceDirect, ProQuest, Scopus, and PubMed. The study's results showed a significant effect of intradialytic exercise on improving physical, cognitive, and sleep quality and quality of life. They could help reduce depression levels in patients undergoing hemodialysis. In conclusion, a structured and adequately monitored intradialysis exercise program is the key to the success of an intradialysis exercise program. Keywords: Hemodialysis, Intradialysis Exercise